A recurred subungual glomus tumour of the thumb. (4th January 2016) - Jalan, Divesh; Elhence, Abhay; Rathore, Devendra Singh; Maley, Deepak Kumar
Abstract : Glomus tumours are rare benign neoplasms arising from the glomus body, accounting for 1–5% of all soft-tissue tumours of the hand. The diagnosis of glomus tumour is frequently delayed, varying from 3 to 15 years. We present a case of a recurred glomus tumour of the thumb where symptoms persisted for a period of 6 years after an attempted surgical excision. The patient presented with classical symptoms of localised tenderness, cold sensitivity and excruciating pain on touch. Findings on radiograph, ultrasonography and contrast-enhanced MRI further supported the diagnosis. Complete surgical excision, the only recommended treatment, resulted in complete symptomatic relief to the patient. This case report highlights the importance of meticulous complete excision and clinical awareness of the disease among primary care physicians.